Pengaruh Komunikasi, Insentif dan Masa Kerja terhadap Kinerja Karyawan: Studi Kasus pada CV Murah Abadi - Rafa Putra Arinda Anugerah; IGG Heru Marwanto; Yogi Yunanto (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to examine the effect of communication, incentives, and tenure on employee performance at CV Murah Abadi. The research uses a quantitative approach with a saturated sampling technique involving 85 employees. Data collection was carried out through questionnaires, interviews, and observations. The results showed that communication, incentives, and tenure had significant partial and simultaneous effects on employee performance. The implications of this study highlight the importance of internal communication quality, a fair incentive system, and the role of employee tenure in improving organizational productivity.